2019
DOI: 10.5194/hess-23-4367-2019
|View full text |Cite
|
Sign up to set email alerts
|

New water fractions and transit time distributions at Plynlimon, Wales, estimated from stable water isotopes in precipitation and streamflow

Abstract: Abstract. Long-term, high-frequency time series of passive tracers in precipitation and streamflow are essential for quantifying catchment transport and storage processes, but few such data sets are publicly available. Here we describe, present, and make available to the public two extensive data sets of stable water isotopes in streamflow and precipitation at the Plynlimon experimental catchments in central Wales. Stable isotope data are available at 7-hourly intervals for 17 months, and at weekly intervals f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 48 publications
5
55
2
Order By: Relevance
“…MTT estimates from 3 H activities combined with those from other techniques would potentially yield complementary information. For example, in catchments where MTTs are months to decades the variations in stable isotopes or Cl may allow a better understanding of the temporal variations in inputs of the very young (<1 year) water components (Botter, 2012; Hrachowitz et al, 2013; Knapp et al, 2019; Visser et al, 2019) that are difficult to study using 3 H. By contrast, 3 H allows the input of water that is more than a few years old at both baseflow and higher streamflows to be assessed. Duvert et al (2016) interpreted variations in δ 18 O values over high flow events in a catchment with 3 H activities significant below those of modern rainfall as reflecting mixing between water with MTTs of a few weeks and baseflow that had MTTs of a few decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTT estimates from 3 H activities combined with those from other techniques would potentially yield complementary information. For example, in catchments where MTTs are months to decades the variations in stable isotopes or Cl may allow a better understanding of the temporal variations in inputs of the very young (<1 year) water components (Botter, 2012; Hrachowitz et al, 2013; Knapp et al, 2019; Visser et al, 2019) that are difficult to study using 3 H. By contrast, 3 H allows the input of water that is more than a few years old at both baseflow and higher streamflows to be assessed. Duvert et al (2016) interpreted variations in δ 18 O values over high flow events in a catchment with 3 H activities significant below those of modern rainfall as reflecting mixing between water with MTTs of a few weeks and baseflow that had MTTs of a few decades.…”
Section: Discussionmentioning
confidence: 99%
“…StorAge Selection Functions consider how waters with different residence times are mobilized relative to the proportion of that water in catchment storage (Benettin, Kirchner, Rinaldo, & Botter, 2015; Benettin, Bailey et al, 2015; Harman, 2015; van der Velde, Torfs, van der Zee, & Uijlenhoet, 2012). Ensemble hydrographs allows the relative contribution of recent precipitation to streamflow over time intervals of hours to days to be made (Kirchner, 2019; Knapp, Neal, Schlumpf, Neal, & Kirchner, 2019). These approaches also require time‐series data, albeit over shorter timescales (individual events or a few months).…”
Section: Introductionmentioning
confidence: 99%
“…For example, if and are sampled daily, "new water" means water that fell within the previous day 90 (and thus is expressed in units of day -1 ), and if they are sampled weekly, "new water" means water that fell within the previous week (and thus is expressed in units of week -1 ). Because the meaning and dimensions of new water fractions depend on the sampling interval, so do the numerical values, as illustrated by Knapp et al (2019). In our example, the weekly event new water fraction, calculated from weekly sampling of the daily values in Fig.…”
Section: Estimating New Water Fractions Using the Function _mentioning
confidence: 99%
“…Ensemble hydrograph separation (EHS) has recently been proposed as a new tool for quantifying catchment transit times, using time series of passive tracers like stable water isotopes or chloride. Benchmark tests using synthetic data have shown that this method should yield quantitatively accurate answers to the questions posed above (Kirchner, 2019), and initial applications to real-world data sets (e.g., Knapp et al, 2019) have demonstrated the potential of this technique. 25…”
Section: Introductionmentioning
confidence: 99%
“…The above methods and modifications were originally designed for single-sample collection using a precipitation totalizer (e.g., IAEA, 2014). For many hydrological questions, however, higher-frequency measurements of stable water isotopes are of interest, requiring daily or even sub-daily sampling of precipitation or streamwater (e.g., Knapp et al, 2019;Rücker et al, 2019;von Freyberg et al, 2018;Wang et al, 2019). This can be achieved with field-deployable automatic water samplers with programmable pump-and-distribution systems that fill and store a series of empty open bottles.…”
Section: Introductionmentioning
confidence: 99%